Whiteness - Adams, Ruth.; Tercier, John.; London Consortium (London : Lawrence & Wishart : London Consortium, Institute of Contemporary Arts, 2000)
Drella plays the whiteman / Ruth Adams ## Groping in the dark / Diana Yeh ## Notown / Mark Morris ## Whiteout / John Tercier ## Pollution of the white cube / Kathy Battista ## The beauty of surfaces / Lorens Holm ## Flicker / Travis Miles ## Metal machine music / Christopher Hight ## White light and its other / Michael Uwemedimo ## Writing on Antarctica / David Tang ## Seeing whiteness in colour / Charles Rice.
Drella plays the whiteman / Ruth Adams -- Groping in the dark / Diana Yeh -- Notown / Mark Morris -- Whiteout / John Tercier -- Pollution of the white cube / Kathy Battista -- The beauty of surfaces / Lorens Holm -- Flicker / Travis Miles -- Metal machine music / Christopher Hight -- White light and its other / Michael Uwemedimo -- Writing on Antarctica / David Tang -- Seeing whiteness in colour / Charles Rice.
Includes bibliographical references.
boek